2022
DOI: 10.1007/s12265-022-10262-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacist-Led Heart Failure Clinic on Optimization of Guideline-Directed Medical Therapy (PHARM-HF)

Abstract: This prospective study included patients with heart failure (HF) with reduced ejection fraction (HFrEF) with LVEF < = 40% to evaluate the impact of pharmacist on guideline directed medical therapy (GDMT). The primary outcome was to compare proportion of triple GDMT achieved for Angiotensin-Converting-Enzyme-Inhibitors (ACEI)/Angiotensin-Receptor-Blockers (ARB)/Angiotensin-Receptor-Neprilysin-Inhibitors (ARNI), beta-blockers, aldosterone antagonists (AA), and quadruple GDMT which in additional to triple therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…These results are similar to those of other trials that demonstrated improved rates of GDMT in the setting of pharmacist-or nurse-led HF treatment optimization. 15,16 These positive results differ from other trials incorporating remote monitoring regarding patient continuation in HT programs. For example, in a study by Ding and colleagues, the withdrawal rate from their monitoring service was about 22%, while in our study only 1 patient withdrew from the HT program.…”
Section: Discussionmentioning
confidence: 76%
“…These results are similar to those of other trials that demonstrated improved rates of GDMT in the setting of pharmacist-or nurse-led HF treatment optimization. 15,16 These positive results differ from other trials incorporating remote monitoring regarding patient continuation in HT programs. For example, in a study by Ding and colleagues, the withdrawal rate from their monitoring service was about 22%, while in our study only 1 patient withdrew from the HT program.…”
Section: Discussionmentioning
confidence: 76%
“…The higher initial incidence highlights the importance of close follow-up during the initiation phase of treatments. Pharmacist-led HF clinics may play a role in these scenarios by timely and accurate protocol-driven dose titration, laboratory monitoring and patient education by pharmacists [26][27][28][29][30]. Further research is warranted to determine the optimal approach for managing these patients and improving outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several efforts have been made to improve compliance with GDMT to overcome clinical inertia. Programs led by medical staff, such as nurses and pharmacists, have been shown to have the potential to lead to improved GDMT practices and better outcomes [9,10]. It may be important for medical teams, including other medical staff, to repeatedly review physician's prescriptions to ensure that GDMT compliance is being practiced where applicable.…”
mentioning
confidence: 99%